2023
DOI: 10.1051/e3sconf/202340307002
|View full text |Cite
|
Sign up to set email alerts
|

Transport Planning of a Metropolis Street Using Simulation Modeling

Alexander Krasnikov,
Irina Nikishina,
Natalia Rebus
et al.

Abstract: This article presents a plan for the development of the area adjacent to Pryanishnikov Street in the Timiryazevsky District of the Northern Administrative District of Moscow. This plan involves upgrading the roadway to distribute traffic flows and isolate the public transport flow. Simulation models are created, reflecting all the objects and rules of interaction that are typical for the studied area to assess the effectiveness of the developed concept. The main feature of the site development plan is the safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Analyses of the outcomes of the conducted research with studies in related fields have shown that using the same methodologies, similar structured results were obtained [3,7,10]. In order to obtain a simulation model of the problem area, the researchers identified all key objects and processes with their qualitative and quantitative features.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Analyses of the outcomes of the conducted research with studies in related fields have shown that using the same methodologies, similar structured results were obtained [3,7,10]. In order to obtain a simulation model of the problem area, the researchers identified all key objects and processes with their qualitative and quantitative features.…”
Section: Discussionmentioning
confidence: 69%
“…In order to visualise the parametric model, a graphical model in the form of a scheme with a detailed explanation of the model elements was developed to increase the clarity and comprehensibility of the process implementation for non-specialists with profile mathematical education. This approach is used in works on related research in the field of management of different business processes [6,10,11]. The obtained simulation model can be used not only in the development of complex hardware and software solutions for the digitalisation of agriculture, but also for the creation of digital educational resources in the training or retraining of crop production specialists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was necessary to create algorithms for the functioning of the expert system; to create digital twins of the objects of the subject area, which are the initial data for the algorithms' work; to determine the specialists who could use the obtained system or the specialists whose activities would be affected. In the works of researchers performing similar tasks, the methods of structural analysis, synthesis, groupings, statistical analysis, observation and expert survey are used [4,6,10].…”
Section: Methodsmentioning
confidence: 99%